KAJIAN ESTETIKA MOTIF UKIRAN MASJID TUO KURANG ASO 60 DI NAGARI PASIR TALANG KABUPATEN SOLOK SELATAN - Yogi Nofriyanto, Drs. Efrizal, M.Pd., Ir. Drs. Heldi, M.Si., Ph.D. (Serupa The Journal of Art Education, 2019)
The purpose of this research is :1. Identify the shape of carving Mosque Tuo Kurang Aso 60 in South Solok. 2. Identify the placement of Carving Mosque Tuo Kurang Aso 60 in South Solok. 3. Describes the content of aesthetic value of Carving Mosque Tuo Kurang Aso 60 in South Solok. This research is located at Nagari Pasir Talang in South Solok.It uses qualitative methods with the descriptive approach. It carried out by field observations, interviews and collection of documentation. For data analysis, by reducing data, presenting data and take aconclusion. To test the validity of data, done by credibility of the data.The results of research found that the shape of carving comes from the shape of plants, animals, and geometry that placement residing on specific areas and contain the same aesthetic value. There are 8 types of traditional Minangkabau engraving motifs. All carving is placed on large and small fields horizontally or vertically on the mosque. On the structure of the building of the mosque is divided into the bottom, the Middle, and the upper part.Key Words: Aesthetics, Carving, Mosque, Form, Placement